Advances in Numerical Methods - Mastorakis, Nikos; Sakellaris, John (Lecture Notes in Electrical Engineering, 2009)
Advances in Numerical Methods provides a balanced presentation of the latest concepts in the fields of applied mathematics, electrical and electronic engineering. It includes many new mathematical applications, numerical schemes, and efficient algorithms as well as the latest research and applications in modeling and simulation, systems theory, circuits, electronics, control and signal processing. The chapters are written by eminent, leading, international experts, who provide up-to-date aspects of the topics discussed and present fresh, original insights into their own experience in these fields. The authors also include methods that also apply to diverse fields such as electronic measurement, computer science, robotics, chemistry, and biology.